2018
DOI: 10.1093/ibd/izy157
|View full text |Cite
|
Sign up to set email alerts
|

Heart Under Attack: Cardiac Manifestations of Inflammatory Bowel Disease

Abstract: There is a well-established association between chronic inflammation and an elevated risk of heart disease among patients with systemic autoimmune conditions. This review aims to summarize existing literature on the relationship between inflammatory bowel disease and ischemic heart disease, heart failure, arrhythmia, and pericarditis, with particular attention to approaches to management and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
1
30
0
5
Order By: Relevance
“…Pericarditis represents the most frequent cardiovascular EIM in IBD patients (70% of the total number of cardiovascular complications) [15, 16]. Its prevalence is 0.19% among the CD patients and 0.23% among the UC patients [17].…”
Section: Epidemiology Of Cardiovascular Eimmentioning
confidence: 99%
“…Pericarditis represents the most frequent cardiovascular EIM in IBD patients (70% of the total number of cardiovascular complications) [15, 16]. Its prevalence is 0.19% among the CD patients and 0.23% among the UC patients [17].…”
Section: Epidemiology Of Cardiovascular Eimmentioning
confidence: 99%
“…The effect of ASCVD related mortality in patients with IBD is debatable[ 12 , 23 , 26 - 29 ]. This can be attributed to multiple factors.…”
Section: Ascvd and Ibdmentioning
confidence: 99%
“…The effects of these agents on cardiac disease observed in rheumatoid arthritis are summarized in Table 2. Both methotrexate and TNF-α antagonists have been associated with a cardioprotective effect due to suppression of systemic inflammation (Barnabe et al, 2011;Lee et al, 2018;Micha et al, 2011;Roubile et al, 2015). These studies have shown prospectively that biological agents reduce the number of adverse cardiac events while this response was not observed in those patients that ceased biological agents during follow-up (Lee et al, 2018).…”
Section: Effect Of Rheumatoid Arthritis Treatment On Myocardial Funmentioning
confidence: 99%
“…As shown in Table 1, inflammatory bowel disease patients present premature signs of subclinical atherosclerosis (Cappello et al, 2017) and increased risk of ischaemic heart disease (IHD), acute myocardial infarction and heart failure (Aniwan, Pardi, Tremaine, & Loftus, 2018; Feng et al, 2017; Fumery et al, 2014). Additional cardiac manifestations are arrhythmias and pericarditis and myocarditis (Mitchell, Harrison, Junga, & Singla, 2018).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%